2022
DOI: 10.1099/mic.0.001168
|View full text |Cite
|
Sign up to set email alerts
|

The FocA channel functions to maintain intracellular formate homeostasis during Escherichia coli fermentation

Abstract: FocA translocates formate/formic acid bi-directionally across the cytoplasmic membrane when Escherichia coli grows by fermentation. It remains unclear, however, what physiological benefit is imparted by FocA, because formic acid (pK a=3.75) can diffuse passively across the membrane, especially at low pH. Here, we monitored changes in intra- and extracellular formate levels during batch-culture fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…When the pH in the periplasmic space of the E. coli cell becomes too acidic, FocA working together with FHL-1 alleviates pH stress [8, 23, 64, 78–80]. In this situation, the proton associated with formic acid might not be relayed back to H209, but instead would be translocated directly into the cytoplasm along with the anion (); this might result from the H209/T91 proton-relay system being overwhelmed by the high concentration of formic acid, with FocA adopting an inwardly directed channel-like function (see ).…”
Section: Role Of Foca In Helping Prevent Acidification Of the Peripla...mentioning
confidence: 99%
See 2 more Smart Citations
“…When the pH in the periplasmic space of the E. coli cell becomes too acidic, FocA working together with FHL-1 alleviates pH stress [8, 23, 64, 78–80]. In this situation, the proton associated with formic acid might not be relayed back to H209, but instead would be translocated directly into the cytoplasm along with the anion (); this might result from the H209/T91 proton-relay system being overwhelmed by the high concentration of formic acid, with FocA adopting an inwardly directed channel-like function (see ).…”
Section: Role Of Foca In Helping Prevent Acidification Of the Peripla...mentioning
confidence: 99%
“…A summary of the amino acid exchanges introduced and tested is shown in Table 1. Cells synthesizing a chromosomally encoded T91A variant of FocA accumulate formate intracellularly, indicating that the threonine residue is particularly important for anion efflux [23]. That serine can partially substitute for threonine suggests that the hydroxyl group of the side chain has a key role in formic acid translocation to the periplasm [66].…”
Section: Essential Role Of T91 In Formate/formic Acid Efflux By Focamentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo assay using a formate‐sensitive fdhF P :: lacZ ‐based reporter was established to study FocA from E. coli (Beyer et al, 2013; Suppmann & Sawers, 1994). The reporter assay allows monitoring of changes in intracellular formate concentration and has shown that H209 is crucial for pH‐dependent uptake of formate by FocA (Kammel, Trebbin, Pinske, et al, 2022), while T91 has an essential function in formate efflux out of the cell (Hunger et al, 2014; Kammel & Sawers, 2022a, 2022b). X‐ray crystal structure data have revealed that T91 can adopt two positions relative to the fixed location of H209; T91 either forms a hydrogen bond with H209, or it moves roughly 5 Å away from it, toward the cytoplasmic vestibule (Lü, Schwarzer, et al, 2012; Waight et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As well as gaining insight into the role of the conserved histidine in bidirectional transporter, the His209Asn mutant grows more poorly than both the wild-type and a strain lacking focA completely, suggesting that allowing efflux only leads to a physiological imbalance that disrupts normal growth. In fact Michelle and Gary have just published another Short Communication in Microbiology to study this further [25], where they study a different focA allele containing a point mutant that makes uptake of formate pH-dependent. Using this strain and similar methods to the first paper they conclude that FocA likely uses different mechanisms for the efflux and uptake of formate that together control the intracellular level of formate.…”
mentioning
confidence: 99%